2010
DOI: 10.1016/j.ejcts.2009.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral thoracoscopic subtotal thymectomy for the treatment of stage I and II thymoma

Abstract: These preliminary results suggest that thoracoscopic thymectomy for Masaoka stage I and II thymoma is technically feasible and safe, and it is less invasive for the patient. Nevertheless, this procedure requires further investigation in a large series with a longer follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 22 publications
3
54
1
2
Order By: Relevance
“…However, it must be clearly stated, that such events occur rarely, usually in less than 10% of patients undergoing thymectomy for thymoma without MG (23,24). On the other hand, some authors proposed subtotal thymectomy in the Masaoka stage I and II thymomas in cases without associated MG (25). However, most of the authors advice to perform a complete thymectomy in thymomas with MG. Thymomas, contrary to the thymic cancer rarely metastasize to the mediastinal lymph nodes, therefore the role of lymphadenectomy of the mediastinum for thymomas is not clear.…”
Section: Indications For Minimally Invasive Thymectomy In Thymoma Witmentioning
confidence: 96%
“…However, it must be clearly stated, that such events occur rarely, usually in less than 10% of patients undergoing thymectomy for thymoma without MG (23,24). On the other hand, some authors proposed subtotal thymectomy in the Masaoka stage I and II thymomas in cases without associated MG (25). However, most of the authors advice to perform a complete thymectomy in thymomas with MG. Thymomas, contrary to the thymic cancer rarely metastasize to the mediastinal lymph nodes, therefore the role of lymphadenectomy of the mediastinum for thymomas is not clear.…”
Section: Indications For Minimally Invasive Thymectomy In Thymoma Witmentioning
confidence: 96%
“…This controversy is, in part, due to the lack of proper definitions as to the meaning of "complete, extended, or maximal thymectomy (17)" and to the fact that some authors have suggested that sub-total thymectomy may be adequate surgery for the treatment of early stage thymomas (18). Not surprisingly, this controversy has mostly come up since the advent of minimally invasive approaches.…”
Section: Controversies In Surgical Managementmentioning
confidence: 98%
“…ET was usually performed in patients who had MG. For these patients, thoracoscopic ET was performed using a bilateral thoracic approach in our institution. STT was defined as the resection of the thymus without the superior and inferior poles in a contralateral thymic lobe (31). Total thymectomy and STT using a unilateral thoracic approach are the main thoracoscopic procedures for thymoma in our institution ( Figure 1).…”
Section: Surgical Treatmentmentioning
confidence: 99%